PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Nadiyah, Farah; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the influence of the financial performance and the firm size to the stock return. The dependent variable is the stock return. Meanwhile the independent variables are firm size and financial performance which is measured by Current Ratio (CR), Return on Assets (ROA), and Price Earning Ratio (PER). The population is all property and real estate companies which are listed in Indonesian Stock Exchange (IDX) in 2011-2015 periods. The sample collection technique has been carried out by using purposive sampling method so 26 property and realestate companies which are listed in the Indonesian Stock Exchange (IDX) have been selected as samples. The data analysist technique has been done by using multiple linear regression analysis and the SPSS 23. The classic assumption test (the test of normalitas, heteroskedastisitas, autokorelasi, and multikolenieritas) is carried out before the multiple regression analysis. Based on the results of hypothesis test shows that return on assets (ROA) give positive influence on stock return whereas the current ratio (CR), price earnings ratio (PER) and firm size give no influence to the stock return.Keywords : Financial Ratio, Firm Size, Stock Return.